(untitled) (Veterinary Science, 2023)
The objective of this trial was to determine the appropriate time to supplement pregnant goats in the San Rafael Department, Mendoza province. 45 adult goats of Creole breed from the South of Mendoza were used. The work was carried out in a ranch in the community of Los Tres Cerritos, located about 110 km south of the city of San Rafael, where extensive goat farming is practiced, with summer transhumance. The first group (GI=n15) was supplemented during the second third of pregnancy, the second group in the last third (GII=n15) and the third one (GIII=n15) was used as a control group. Feeding was carried out extensively and freely, on a recovering natural pasture in the region, which corresponds to a transition zone between the Monte Region and Patagonia. The supplementation consisted, in all cases, on a daily ration of 500 grams of bales of alfalfa and 250 grams of broken corn, upon return from grazing. Goats were weighed with an electronic scale of 100 kg maximum and 50 grams of precision at the time of service, at the end of the second third of gestation, at the end of the third third of gestation, 2 days after calving and at weaning time; while the pups were weighed at birth, 15, 45 and 60 days of age. The experimental design responded to a completely randomized model and the means and standard deviations were studied by Analysis of Variance and Tukey’s Test, applying the statistical package InfoStat 2.0.